2000
DOI: 10.1097/00001756-200006260-00024
|View full text |Cite
|
Sign up to set email alerts
|

Sleep deprivation stimulates serotonin release in the suprachiasmatic nucleus

Abstract: Recent literature suggests that sleep deprivation has a general stimulatory effect on the central serotonergic system. Herein we report that in hamsters, sleep deprivation induced by gentle handling for 3 h under dim red light at midday stimulates serotonin release in the suprachiasmatic nuclei by as much as 171%. Basal levels of 5-HT release are re-established within 1 h after cessation of treatment. Sleep deprivation also evokes phase advances of the circadian activity rhythm averaging 2 h. When sleep depriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
58
0
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(63 citation statements)
references
References 12 publications
4
58
0
1
Order By: Relevance
“…Furthermore, like antidepressant treatment, TSD in rats stimulates hippocampal neurogenesis (Grassi Zucconi et al, 2006). It has also been shown in hamsters that TSD affects serotonin levels in the SCN and other brain regions, and results in a strong phase advance in activity rhythms (Asikainen et al, 1995;Grossman et al, 2000). These studies are just beginning, and are important in determining the mechanism underlying the therapeutic effects of TSD as an antidepressant.…”
Section: Treating Mood Disorders By Altering the Circadian Cycle 41 mentioning
confidence: 96%
“…Furthermore, like antidepressant treatment, TSD in rats stimulates hippocampal neurogenesis (Grassi Zucconi et al, 2006). It has also been shown in hamsters that TSD affects serotonin levels in the SCN and other brain regions, and results in a strong phase advance in activity rhythms (Asikainen et al, 1995;Grossman et al, 2000). These studies are just beginning, and are important in determining the mechanism underlying the therapeutic effects of TSD as an antidepressant.…”
Section: Treating Mood Disorders By Altering the Circadian Cycle 41 mentioning
confidence: 96%
“…It is well established that light and glutamate agonists inhibit non-photic phase shifts (Mrosovsky, 1991;Grossman et al, 2000;Hall et al, 1999;Gamble et al, 2004;Biello et al, 1997;Prosser, 2001). Further, we have shown that non-photic phase shifts, including in vitro serotonergic phase shifts, are enhanced by a treatment (enzymatic removal of polysialic acid) that inhibits glutamate signaling in the SCN (Fedorkova et al, 2002).…”
Section: Ethanol Enhancement Of Serotonergic Phase Shifts Could Occurmentioning
confidence: 99%
“…Moreover, there is a mutually antagonistic relationship between non-photic stimuli that induce daytime phase shifts and photic input mediating nighttime phase shifts. Light or glutamate stimulation during the day inhibits non-photic phase shifts (Mrosovsky, 1991;Grossman et al, 2000;Hall et al, 1999;Gamble et al, 2004;Biello et al, 1997;Prosser, 2001;Kallingal and Mintz, 2007), while nighttime presentation of non-photic stimuli suppresses light/glutamate-induced phase shifts (Ralph and Mrosovsky, 1992;Yannielli and Harrington, 2004;Smith et al, 2001;Gamble et al, 2004;Biello et al, 1997;Kallingal and Mintz, 2007). Conversely, suppressing glutamate signaling during the day can enhance phase shifts induced by non-photic stimuli (Fedorkova et al, 2002), while decreasing neuropeptide Y or 5-HT signaling at night can enhance photic phase shifts (Yannielli and Harrington, 2004;Lall and Harrington, 2006;Smart and Biello, 2001;Muscat et al, 2005).…”
mentioning
confidence: 99%
“…The procedures used for sleep deprivation were similar to those used in a previous study (Grossman et al, 2000). Beginning at ZT 6, animals outfitted with a microdialysis probe in the SCN and an injection reentry cannula aimed at the DRN were aroused and maintained in the waking state in their home cage for 3 hr by continuous gentle handling and light puffs of air.…”
Section: Effects Of Intra-drn 5-ht Antagonists On Sleep Deprivation-imentioning
confidence: 99%
“…For example, there is evidence that 5-HT acts in the SCN to mediate the clock-resetting effects of behavioral stimulation. This includes findings that 5-HT agonists applied to the SCN in vitro or in vivo reset circadian phase (Prosser et al, 1990Medanic and Gillette, 1992;Challet et al, 1998;Ehlen et al, 2001) and that behavioral phaseresetting manipulations evoke SCN 5-HT release (Dudley et al, 1998;Grossman et al, 2000). Conversely, reports that raphe lesions (Meyer-Bernstein and Morin, 1998), treatment with 5-HT antagonists (Antle et al, 1998), or depletion of 5-HT in the SCN (Bobrzynska et al, 1996) do not block behavioral phase shifting argue against a role of 5-HT in circadian clock resetting.…”
Section: Introductionmentioning
confidence: 99%